The Spanish innovative firm and the ESPRIT, RACE and EUREKA programmes an organizational approach - Barañano, Ana Maria (Technovation)
The aim of this study is to analyse the organizational and managerial factors leading to innovative success in Spanish firms, and the link between these factors and their position in European collaborative R&D programmes. The research is based on interviews with 51 Spanish companies. The results have shown that, in Spain, there is a small group of firms performing an integrated innovative effort, thus reaching the highest level of innovative success. These ideal firms were the ones proposing the largest number of R&D projects to the European institutions, and at the same time, obtaining the highest rate of approval. However, these companies complain greatly about the bureaucratic procedures associated with the European R&D collaboration process. Moreover, given the high-tech level of these enterprises, European cooperation in R&D offers fewer advantages to them than to other technologically less developed firms. This study provides some interesting ideas, on the other hand, for the management of innovation, especially when it is performed in a collaborative scheme; and, on the other hand, for Spanish participation in European technological initiatives.